Fish Diversity in Namang River, Bangka Tengah Regency, Bangka Belitung Province - Helmizuryani Helmizuryani; Muhammad Nizar; Khusnul Khotimah; Meika Puspita Sari; Innike Abdillah Fahmi; Robin Robin; Tri Deniansen; Swarlanda Swarlanda (Journal of Global Sustainable Agriculture, 2024)
The Namang River is a small river located in Central Bangka District, Bangka Belitung Province. Bangka Island is known to have high biodiversity, both plants and animals, including freshwater fish species. Based on information, there are several types of fish that are endemic fish that are only found in the Namang River. Climate change and changes in land use due to tin mining activities can threaten the survival of fish species in the Namang River. This research aims to analyze fish diversity and fish habitat conditions in the waters of the Namang River, Central Bangka, Bangka Belitung Province. Based on the research results, 15 species of fish, 1 species of shrimp and 1 species of freshwater crab were found. The species with the highest abundance are Trigonopoma gracilie and Trigonopoma pauciperforatum. Of the 15 species, three species are endemic to Bangka Island, namely Betta chloroparynx, Parosphromenus deissneri, and Betta schalleri.